Depressive state associated with cryptogenic rigid person syndrome (case study) - Aleksandr G. Naryshkin; Mikhail N. Klochkov; Taras A. Skoromets; Igor V. Galanin; Sergey A. Katyshev; Aleksandr V. Vtorov; Ilya A. Orlov; Khalid Kh. Umaev (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The article describes peculiarities of modern understanding of the nature and treatment of the rigid person syndrome. Baclofen, a GABA-B agonist, is one of the drugs of choice for the treatment of this condition. However, its oral use has little efficacy and leads to a number of complications. An indisputable alternative to oral administration of the drug at present is its continuous intrathecal administration using an implantable pump. A case of cryptogenic rigidity syndrome accompanied by the development of a depressive state is presented. In the process of treatment by intrathecal baclofen therapy, not only excruciating muscle spasms disappeared, but also depressive symptomatology without special use of antidepressants.The purpose of the study. To show the high effectiveness of ITT in a patient with a severe cryptogenic form of CRS, as well as the effect of OT, not only on spasticity, but also on depressive symptoms.Material and methods. A case of treatment by the ITB method with implantation of a pump to a patient with a cryptogenic form of HPV is presented. A modified Ashworth scale (MAS) was used to assess spasticity. The patient’s quality of life was assessed on the Barthel scale. The Hamilton scale was used to assess the level of depression.